2014
DOI: 10.1080/02739615.2014.948164
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Environmental Consequences of Ticcing in Youth With Chronic Tic Disorders: The Tic Accommodation and Reactions Scale

Abstract: Tics associated with Tourette syndrome and other chronic tic disorders (CTDs) often draw social reactions and disrupt ongoing behavior. In some cases, such tic-related consequences may function to alter moment-to-moment and future tic severity. These observations have been incorporated into contemporary biopsychosocial models of CTD phenomenology, but systematic research detailing the nature of the relationship between environmental consequences and ticcing remains scarce. This study describes the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Aversive experiences resulting from tics, such as pain during tics, bullying by peers, or attracting attention from others, are thought to be associated with premonitory urges [31]. If the patient does not perform tasks that he or she doesn't want to do (i.e., homework or errands) because of tic symptoms, the onset or progression of premonitory urges will be affected [31][32][33][34]. In a study of adolescents aged 9 to 17 years old, Rozenman et al [35] reported that the severity of anxiety and panic symptoms or somatic symptoms assessed using the Screen for Child Anxiety-Related Emotional Disorders-Child Version is associated with the PUTS score.…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…Aversive experiences resulting from tics, such as pain during tics, bullying by peers, or attracting attention from others, are thought to be associated with premonitory urges [31]. If the patient does not perform tasks that he or she doesn't want to do (i.e., homework or errands) because of tic symptoms, the onset or progression of premonitory urges will be affected [31][32][33][34]. In a study of adolescents aged 9 to 17 years old, Rozenman et al [35] reported that the severity of anxiety and panic symptoms or somatic symptoms assessed using the Screen for Child Anxiety-Related Emotional Disorders-Child Version is associated with the PUTS score.…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…Additionally, emerging data suggests that expression of tic symptoms can also result in environmental consequences [17]. For instance, it has been a common clinical observation in youth with TS to have family members accommodate tic expression in efforts to reduce the intensity and/or frequency of tics.…”
mentioning
confidence: 99%
“…1 Meanwhile positive environmental contingencies (e.g., rewarding the child for using a competing response) were associated with positive outcomes. Providing further preliminary data on accommodation in TS samples, Capriotti et al [17] developed the Tic Accommodation and Reactions Scale (TARS), an assay of tic-related environmental consequences. While not a direct assessment of family accommodation, the subscales included a variety of tic-related environmental consequences, including attention, escape, and aversive consequences across home, school, and public settings.…”
mentioning
confidence: 99%
“…However, recent relevant studies have seldom used these tools, given the limitations of self‐reporting in children. Although some studies have used the Premonitory Urge for Tics Scale (PUTS) to evaluate tic‐related premonitory urges, this tool does not assess tics; rather, it is a 10‐item scale that assesses 10 somatic sensations related to tics. The scores from this scale range from 0 (never) to 4 (severe).…”
Section: Behavioral Assessments Of Pmdsmentioning
confidence: 99%